The relationship between brand reliability and behavioral inclinations, concerning the mediation role of perceptual consequences of Brand (Case study: Adidas store in Tehran) - Eskandarpour, Behrouz (Revista de la Universidad del Zulia, 2019)
Concerning the sensitive competitive condition in the world, each store in order to achieve its superior aims, namely, fundraising and increasing business efficiency alongside all problems and official disciplines (official provisions, note office), needs to possess hardworking, energetic, considerate, and liable personnel for attracting and retaining customers. This research was done in Adidas store of Tehran, with the purpose of investigating the relationship between brand reliability and behavioral inclinations, concerning the mediation role of perceptual consequences of Brand. This study is a practical one and data collection method was descriptive and survey based. The statistical community consisted of whole customers of Adidas store in Tehran. To examine research hypothesis a sample of 400 customers were selected randomly. For data collection regarding literature of research, library method was used (studying books and articles) and for hypothesis testing standard questionnaire was used based on 5- point Likert scale. Reliability of questionnaire was confirmed by experts and respective professors’ point of view. Reliability coefficient based on Cronbach’s alpha was calculated (0.921). For data analysis, confirmatory factor analysis and structural equation modeling were used. The results of study showed that, brand reliability has a positive impact on customer satisfaction, loyalty and commitment, and continuous commitment of customers. Also, customer satisfaction, loyalty and commitment have a positive impact on inclinations to oral advertising, and it was observed that, when customer satisfaction, loyalty and commitment are high, customers’ tendency for changing store will decrease.